Comprehending Secondary School Underperformance from The Perspective of Psychosocial Factors - Nghonyama, Miyelani; Modiba, Ngoako (Journal of Posthumanism, 2026)
This paper examines the underperformance of secondary schools through a psychosocial lens within a qualitative, empirical framework grounded in Bandura’s Social Learning Theory. Using a case study design, data were collected through interviews and observations from five persistently underperforming secondary schools in the Vhembe District. Participants included principals, educators, learners (RCL members), and parents (SGB members). Thematic content analysis and the constant comparative method were used to interpret the data. Findings reveal three key psychosocial contributors to poor performance: street-hawking, which distracts learners; an unclean schooling environment, which hampers focus; and initiation rites, which delay academic progress. The study concludes that psychosocial factors play a significant role in school underperformance and should not be overlooked. It recommends that schools adopt proactive measures to identify and mitigate these factors to enhance academic outcomes.